2014
DOI: 10.1109/tnet.2013.2286624
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the QoE of Rate Changes in Skype/SILK VoIP Calls

Abstract: The effective end-to-end transport of delay-sensitive voice data has long been a problem in multimedia networking. One of the major issues is determining the sending rate of real-time VoIP streams such that the user experience is maximized per unit network resource consumed. A particularly interesting complication that remains to be addressed is that the available bandwidth is often dynamic. Thus, it is unclear whether a marginal increase warrants better user experience. If a user naively tunes the sending rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Note that prior work [15] has shown that 30 people are sufficient to generate significant statistics. 60 is twice the amount to further enhance the confidence and so that the total payment to Amazon and the workers are controlled within our budget.…”
Section: User Demographymentioning
confidence: 99%
“…Note that prior work [15] has shown that 30 people are sufficient to generate significant statistics. 60 is twice the amount to further enhance the confidence and so that the total payment to Amazon and the workers are controlled within our budget.…”
Section: User Demographymentioning
confidence: 99%
“…The research community has established a body of work that investigated several of the influencing factors [1] for QoE in video-conferencing. In the main focus are the system factors, with aspects like audio and video quality [6,14,40,43,62], audiovisual synchronization [58] and delay [51,59]. Further studies regarding non-technical influencing factors have looked into interaction [20,47,59], the user state, such as engagement [52] and contextual factors like different devices [10,66].…”
Section: Subjective Studies Investigating Qoe In Video-conferencingmentioning
confidence: 99%
“…The correlation between the stability of the connection and the QoE is considered in [22], [23]; we do not consider the variability of network conditions in our work but as long as variability is measurable, it can be introduced in our methodology and used to calibrate the model.…”
Section: Related Workmentioning
confidence: 99%